Experiences and lessons learned from a patient‐engagement service established by a national research consortium in the U.S. Veterans Health Administration - Tracy L. Sides; Agnes C. Jensen; Malloree M. Argust; Erin C. Amundson; Gay R. Thomas; Rebecca Keller; Mallory Mahaffey; Erin E. Krebs (Wiley, 2024)
Abstract Introduction Meaningful engagement of patients in the research process has increased over the past 20 years. Few accounts are available of engagement infrastructure and processes used by large research organizations. The Pain/Opioid Consortium of Research (Consortium) is a U.S. Department of Veterans Affairs (VA) research network that provides infrastructure to accelerate health research and implementation of evidence‐based health care. The Consortium's key activities include facilitating Veteran‐engaged research and building community between Veterans and VA researchers. This report sought to describe experiences and lessons learned from the first 3 years of a national research engagement service, featuring a Veteran Engagement (VE) Panel, established by the Consortium. Methods We gathered authors' experiences to describe development and operation of the Consortium's VE Panel. Engagement staff collected program evaluation data about partners (Veterans and researchers), projects about which the VE Panel consulted, and meeting attendance during operation of the engagement service. Results We created a 12‐member VE Panel; all of whom had lived experience with chronic pain, prescription opioid medication use, or opioid use disorder. Engagement staff and VE Panel members implemented an engagement service operational model designed to continuously learn and adapt. The panel consulted on 48 projects spanning the research process. Seventy‐eight percent of panel members, on average, attended each monthly meeting. VE Panel members and participating researchers reported high satisfaction with the quality, ease, and outcomes of their engagement service experiences. Conclusions This work provides an illustrative example of how a national research consortium facilitated Veteran‐engaged research and built community between Veterans and VA researchers by developing and operating an ongoing engagement consulting service, featuring a VE Panel. The service, designed as a learning community, relied on skilled engagement staff to cultivate high quality experiences and outcomes for all partners.